Holistic pedagogy for nurturing faithful, resilient and empathetic students - in UNTAG Semarang architectural education - Eko Nursanty; Loekman Muhamadi; Anwar Anwar (Universitas 17 Agustus 1945 Semarang, Indonesia, 2019)
Nowadays education is often seen as a way to improve the